The Rabies Free Burkina Faso initiative: an example of how one health-oriented civil society organizations can contribute towards the achievement of the rabies zero by 30 goal - Savadogo, M.; Dahourou, L.D.; Ilboudo, Abdoul K.; Ilboudo, Guy S.; Zangré, H.; Tarnagda, G.; Souli, Z.; Combari, A.H.B.; Diarra, R.; Bidima, M.; Traoré, M.G.B.; Mandé, C.D.; et al. (Springer, 2023)
While technologies, tools and expertise have proven that countries can be made safe from dog-mediated human rabies, the disease remains a major public health threat in Burkina Faso. The paper reports the experience and success stories of Rabies Free Burkina Faso, an initiative established in 2020 as an example of civil society organization that promotes One Health for integrated rabies control in Africa. As recommended in the Global strategic plan, rabies elimination requires a systematic One Health approach, enhancing pre-exposure and postexposure prophylaxis, dog population management, dog vaccination, awareness raising, diagnosis, surveillance, funding as well as policies and regulations. Rabies Free Burkina Faso was established on 28 September 2020 as not-for-profit organization and aims to strengthen the use of a One Health approach as a non-governmental, multidisciplinary initiative dedicated to promoting rabies elimination. Categories of interventions developed by Rabies Free Burkina Faso cover awareness raising, training and One Health capacity building, dog rabies vaccination, seeking vaccines and providing support, including financial resource to communities to ensure that bite victims are appropriately provided with post-exposure prophylaxis, research, community engagement and joint outbreak investigation in collaboration with competent authorities. Reported success stories confirm the relevance of roles that can be played by Rabies Free Burkina Faso supporting animal health and human health authorities in the fields of rabies control and One Health development in the country.